Estradiol-Induced Enhancement of Object Memory Consolidation Involves Hippocampal Extracellular Signal-Regulated Kinase Activation and Membrane-Bound Estrogen Receptors - Fernandez, Stephanie M. (Society for Neuroscience, 2008)
The extracellular signal-regulated kinase (ERK) pathway is critical for various forms of learning and memory, and is activated by the potent estrogen 17β-estradiol (E(2)). Here, we asked whether E(2) modulates memory via ERK activation and putative membrane-bound estrogen receptors (ERs). Using ovariectomized mice, we first demonstrate that intraperitoneal injection of 0.2 mg/kg E(2) significantly increases dorsal hippocampal levels of phosphorylated ERK protein 1 h after injection. Second, we show that E(2) administered intraperitoneally (0.2 mg/kg) or via intrahippocampal infusion (5.0 μg/side) immediately after training in an object recognition task significantly enhances memory retention, and that the beneficial effect of intraperitoneal E(2) is blocked by dorsal hippocampal inhibition of ERK activation. Third, using bovine serum albumin-conjugated 17β-estradiol (BSA-E(2)), we demonstrate that E(2) binding at membrane-bound ERs can increase dorsal hippocampal ERK activation and enhance object memory consolidation in an ERK-dependent manner. Fourth, we show that this effect is independent of nuclear ERs, but is dependent on the dorsal hippocampus. By demonstrating that E(2) enhances memory consolidation via dorsal hippocampal ERK activation, this study is the first to identify a specific molecular pathway by which E(2) modulates memory and to demonstrate a novel role for membrane-bound ERs in mediating E(2)-induced improvements in hippocampal memory consolidation.